Management of Meloidogyne incognita associated with okra (Abelmoschus esculentus) using moringa (Moringa oleifera) - Aminisarteshnizi, Mehrnoush (Tropical Agriculture, 2024)
Okra is one of the important vegetable crops grown in tropical and sub-tropical areas worldwide. Different parts of the crop, including fresh leaves, buds, flowers, pods, stems, and seeds, are usable. Okra contains various benefits for humans, including fibre and vitamins. One of the critical pests for okra is root-knot nematode which causes crop yield loss. Therefore, an investigation was conducted in 2022 at the Aquaculture Research Unit laboratory at the University of Limpopo to evaluate the effectiveness of moringa (Moringa oleifera) application in controlling root-knot nematode in okra. During a survey of an okra field, Meloidogyne incognita was identified from the root samples. Leaf and fruit powder of moringa, along with positive control (fenamiphos) and a negative control (tap water), were used to study their efficacy against M. incognita. In pot trials, seedlings of okra were inoculated with 3000 eggs and second-stage juveniles (J2) of M. incognita; with treatments comprising leaf and fruit powder of moringa; 56 days after inoculation, the moringa leaf and fruit powder treatments compared to the negative control had, respectively, 69.2 and 56.4% fewer eggs and J2 in soil; 84.2 and 74.5% lower gall number; and 69.6 and 36.6% lower gall index. by 56.4 – 69.2%. The percentage improvements for the positive control were not significantly different from those for moringa leaf powder (P > 0.05). These results showed that moringa leaf powder is promising for controlling root-knot nematode in okra.
Journal article published in Tropical Agriculture Journal (Trinidad) Vol 101 No. 1 January 2024
Keywords: Moringa oleifera; Biological control; Okra; Meloidogyne incognita; Moringa; Root-knot nematode; Moringa oleifera; Okra; Root knot nematode